A brief transdiagnostic pandemic mental health maintenance intervention. Issue 3 (2nd October 2021) - Arnold, Trisha; G. Rogers, Brooke; L. Norris, Alyssa; Schierberl Scherr, Anna; Haubrick, Kayla; E. Renna, Megan; Sun, Shufang; M. Danforth, Margaret; T. Chu, Christina; S. Silva, Elizabeth; Whiteley, Laura B.; Pinkston, Megan
ABSTRACT: The COVID-19 pandemic qualifies as a major national and global disaster. Behavioral health providers are poised to provide psychological crisis interventions to reduce the psychosocial effects. This paper presents a brief transdiagnostic mental health maintenance intervention tailored to treat adults and families with distress symptoms. The intervention components include evidence-based techniques which have been strategically selected to address distress related to the pandemic and to prevent the escalation of distress. The intervention aims to be flexibly incorporated into care based on the provider and needs of the presenting individuals. The intervention incorporates components of evidence-based treatments such as Cognitive Behavioral Therapy and associated "third wave" therapies (e.g. Dialectical Behavioral Therapy and Acceptance and Commitment Therapy). The intervention can be delivered via telehealth and includes the following modules: 1) Agenda Setting & Avoidance Identification; 2) Responding to Difficult News/Normalizing Reactions; 3) Perspective Taking; 4) Situational Control/Acceptance; 5) Maintaining a Healthy Routine; 6) Coping with Stress; 7) Insomnia Preventions; and 8) Building Resiliency & Hope. The intervention includes a list of home based pleasurable activities, a list of technology modalities to maintain social interactions, and a handout for patients. Research is needed to further test this intervention and assess implementation strategies.